Free gingival grafting technique for gingival recession coverage: A 6-month follow-up interventional study - Rajendran, Poornima; Namburi, Rajesh (Eastern Journal of Medical Sciences, 2024)
Background: Both the practitioner and the patient frequently deal with gingival recession. In Miller’s Classes I and II mandibular gingival recession, the goal of this study was to evaluate the predictability of the free gingival graft (FGG), as a single-step operation in terms of root coverage and esthetics. Materials and Methods: 10 patients between the ages of 25 and 50 who were sent to the Department of Periodontics (3 men and 7 women) made up the study group. There were a total of 14 mandibular recession sites that were chosen. Recession depth (RD), recession width, probing depth (PD), clinical attachment level (CAL), width of attached gingiva (WAG), and visual analog scale (VAS) were assessed at baseline, 3 months, and 6 months post-operatively. Results: The mean RD was 3.13±2.0 mm at the baseline and decreased to 0.80±0.78 mm after 6 months. At baseline, the VAS was 3.52±0.81, and at 6 months after surgery, it had improved to a mean of 6±2.14. From a baseline WAG of 0.35±0.38 to 2.83±0.68 mm, there wasa significant increase with p